A hydrophilized magnetic nanomaterial and its preparation method and application in phosphorylated protein / peptide enrichment
By using dextran polymer grafted phosphate-modified composite magnetic nanomaterials, the specific limitation and high cost of phosphorylated protein/peptide enrichment in the prior art are solved, efficient and selective phosphorylated peptide enrichment is achieved, and mass spectrometry identification ability is significantly improved.
Patent Information
- Application Number
- CN202410826733.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The prior art has specific limitations, high cost and false positive problems in the enrichment of phosphorylated proteins/peptides, and poor mass spectrometry response, resulting in limited development of phosphorylated proteomics research.
Compound magnetic nanomaterials modified with dextran polymer grafted phosphate are used to induce atom transfer radical polymerization reaction through the surface, introduce a large number of modified sites, and fix Ti4+ through functional modification to form a new magnetic nanomaterial with high hydrophilicity and specific surface area.
The enrichment efficiency and selectivity of phosphorylated peptides are significantly improved, the mass spectrometry signal intensity and identification number are enhanced, the enrichment of non-phosphorylated peptides is reduced, and the enrichment specificity and repeatability are improved.
Smart Images

Figure CN118719016B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of analytical chemistry. Specifically, the present invention relates to a hydrophilized magnetic nanomaterial and a preparation method thereof and application in phosphorylated protein / peptide enrichment. More specifically, the hydrophilized magnetic nanomaterial is a novel composite magnetic nanomaterial modified by a dextran polymer grafted with a phosphate. Background Art
[0002] Protein phosphorylation is one of the most common and important post-translational modifications (PTMs); it is involved in the regulation of a variety of cellular life processes, such as cell cycle control, DNA damage response, transcription, protein transport, metabolism, and programmed cell death. Phosphorylation events play a key role in cell signaling and are associated with the occurrence of many human diseases, such as cancer, Parkinson's disease, cardiovascular disease, and many other diseases. Accurate identification of phosphorylated proteins, precise identification of phosphorylation sites, and monitoring of the temporal dynamics of protein phosphorylation in response to cellular perturbations are essential for understanding the mechanisms behind disease pathology and promoting the development of new biomarkers and therapeutic agents. Mass spectrometry (MS) has always been the main technical means for major scientific breakthroughs and plays a core role in the study of protein phosphorylation. However, the current phosphoproteomic research based on mass spectrometry is still facing a series of problems, mainly because of the low abundance of phosphorylated proteins / peptides, low ionization efficiency, and poor mass spectrometry response, which makes mass spectrometry identification extremely difficult and limits the development of phosphoproteomic research. Therefore, selective enrichment of phosphorylated proteins / peptides from complex biological environments before mass spectrometry detection has become a necessary prerequisite for phosphorylated protein research. So far, various affinity materials have been developed for the enrichment of phosphorylated biomolecules, mainly including immunoprecipitation, ion exchange chromatography, immobilized metal ion affinity chromatography (IMAC) and metal oxide affinity chromatography (MOAC) techniques. Immunoprecipitation is a common method for enriching phosphorylated proteins. This method has high selectivity and is very effective for enriching proteins containing specific phosphorylation sites. However, immunoprecipitation methods for enriching phosphorylated proteins still have many disadvantages, such as specificity limitations, high costs, and possible false positives. Ion exchange chromatography uses different ion exchangers to separate charged substances, including negatively charged phosphorylated peptides. However, ion exchange chromatography is usually separated based on the charged properties of peptides, but the charged properties of phosphorylated peptides may be affected by other modifications or peptide chain length, so the enrichment specificity is low, resulting in the enrichment of some non-phosphorylated peptides. Therefore, this enrichment method is often used as a pre-separation tool for peptides. In recent years, affinity chromatography-based methods such as immobilized metal ion affinity chromatography (IMAC) and metal oxide affinity chromatography (MOAC) have developed rapidly. Both immobilized metal ion affinity chromatography (IMAC) and metal oxide affinity chromatography (MOAC) are commonly used methods for purifying phosphorylated proteins. IMAC achieves selective enrichment of phosphorylated peptides by forming complexes between metal ions and phosphate groups in phosphorylated peptides. This method has high selectivity and sensitivity. The principle of MOAC is similar to that of IMAC, but MOAC uses metal oxides instead of metal ions to specifically interact with target phosphorylated proteins. However, compared with IMAC, the specificity of MOAC is poor.The low density of immobilized metal ions, strong nonspecific adsorption of acidic nonphosphorylated peptides, and easy loss of interacting ions have seriously hindered the further development of immobilized metal ion affinity chromatography (IMAC). Dextran polymers are non-toxic, biocompatible, water-soluble, and degradable, and are often used for surface functionalization of MNPs. The modification of dextran polymers introduces many metal ion chelating sites and significantly reduces nonspecific adsorption losses. In addition, dextran polymers endow nanoparticles with excellent selectivity. Dextran-modified magnetic nanoparticles have a large number of hydroxyl groups and can be modified in various ways, providing an ideal enrichment platform for mass spectrometry analysis of phosphopeptides. Summary of the invention
[0003] In view of this, in order to overcome the above-mentioned technical problems existing in the art, the object of the present invention is to provide a hydrophilic magnetic nanomaterial and a preparation method thereof and application in phosphorylated protein / peptide enrichment.
[0004] The present invention adopts the following technical solutions to achieve the above-mentioned invention objectives:
[0005] The first aspect of the present invention provides a method for preparing a novel composite magnetic nanomaterial modified by glucan polymer grafted with phosphate.
[0006] Further, the method comprises the following steps: using 2-methylacrylate 3-glucose aminopropyl ester GMA-G as a polymerization monomer, cuprous chloride as a catalyst, 1,1,4,7,7-pentamethyldiethylenetriamine as a ligand, fixing the SI-ATRP initiator on Fe 3 O 4 @SiO 2 After the surface, GMA-G was introduced, and Fe 3 O 4 @SiO 2 Surface-initiated SI-ATRP reaction generates Fe 3 O 4 @SiO 2 @GMA-G, aldehyde, amino, and phosphate groups are chemically modified to Fe 3 O 4 @SiO 2 @GMA-G surface and immobilization of Ti on phosphate groups 4 + , a new type of composite magnetic nanomaterial Fe modified by dextran polymer grafted phosphate 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ .
[0007] Furthermore, the molar ratio of the polymerization monomer, the catalyst and the ligand is 100-400:1:1-3;
[0008] Preferably, the molar ratio of the polymerization monomer, the catalyst and the ligand is 100:1:1.5;
[0009] Preferably, the SI-ATRP reaction is carried out in an organic solvent;
[0010] More preferably, the organic solvent is methanol;
[0011] Preferably, the reaction conditions of the SI-ATRP reaction are 60° C. and stirring for 3 h.
[0012] Furthermore, the GMA-G was prepared by the following method: glycidyl methacrylate was subjected to a first oxidation reaction with 0.2 M sulfuric acid at 50° C. for 4 h, sodium periodate was added, and the reaction was carried out at room temperature in the dark for 4 h for a second oxidation reaction, 0.5 M glucosamine hydrochloride and 1% NaBH 3 CN is dissolved in methanol containing NaOH, and the oxidation product is mixed with a methanol solution of glucosamine, and a Schiff base reaction is carried out at room temperature for 4-12 h to obtain GMA-G;
[0013] Preferably, the molar ratio of glycidyl methacrylate, sulfuric acid, sodium periodate, and glucosamine hydrochloride is 1:0.25-1:0.5-2:0.5-2;
[0014] More preferably, the molar ratio of glycidyl methacrylate, sulfuric acid, sodium periodate and glucosamine hydrochloride is 1:0.4:1:1.
[0015] Further, the SI-ATRP initiator is prepared by the following method: 3-aminopropyltriethoxysilane and triethylamine are added to tetrahydrofuran, the mixed solution is deoxygenated with nitrogen and kept reacting in an ice bath for 30 minutes, 2-bromoisobutyryl bromide is slowly added dropwise to the mixed solution and vigorously stirred for 4 hours to obtain the SI-ATRP initiator;
[0016] Preferably, the dosage of 3-aminopropyltriethoxysilane is 1.875 mL, 8 mmol;
[0017] Preferably, the dosage of triethylamine is 1.4 mL, 10 mmol;
[0018] Preferably, the dosage of tetrahydrofuran is 12.5 mL;
[0019] Preferably, the dosage of 2-bromoisobutyryl bromide is 1.25 mL, 10 mmol.
[0020] Further, the Fe 3 O 4 @SiO 2 It was prepared by the following method: FeCl 3 6H 2 O was dissolved in ethylene glycol, ultrasonically dissolved, anhydrous sodium acetate was added, and after dissolution, the resulting uniform solution was reacted at 220°C for 8h to obtain Fe 3 O 4 , Fe 3 O 4 Dispersed in a mixture of ethanol, water and concentrated ammonia, added ethyl orthosilicate, stirred at 30°C for 6 hours, and obtained Fe 3 O 4 @SiO 2 ;
[0021] Preferably, the FeCl 3 6H 2 The dosage of O is 2.70 g;
[0022] Preferably, the dosage of ethylene glycol is 100 mL;
[0023] Preferably, the dosage of anhydrous sodium acetate is 7.20 g;
[0024] Preferably, the Fe 3 O 4 The dosage is 350mg;
[0025] Preferably, the dosages of ethanol, water and concentrated ammonia are 160 mL, 40 mL and 1.5 mL respectively;
[0026] Preferably, the dosage of the tetraethyl orthosilicate is 1.0 mL.
[0027] Furthermore, the SI-ATRP initiator was fixed on Fe 3 O 4 @SiO 2 The surface comprises the following steps: 3 O 4 @SiO 2 Mix evenly with the methanol solution containing SI-ATRP initiator and dehydrate for 12 hours;
[0028] Preferably, the dosage of the SI-ATRP initiator is 500 μM;
[0029] Preferably, the dosage of methanol is 500 μL;
[0030] Preferably, the dehydration reaction is carried out at 37°C.
[0031] Further, the aldehyde group was modified to Fe by the following method. 3 O 4 @SiO 2 @GMA-G surface: using NaIO 4 With the Fe 3 O 4 @SiO 2 @GMA-G reaction to obtain aldehyde-modified Fe 3 O 4 @SiO 2 @GMA-G;
[0032] Preferably, the NaIO 4 The dosage used was 10 mM, 500 μL;
[0033] Preferably, the following method is used to modify the amino group to the aldehyde-modified Fe 3 O 4 @SiO 2 @GMA-G surface: The aldehyde-modified Fe 3 O 4 @SiO 2 @GMA-G and ethylenediamine mixed solution were mixed and reacted in a water bath to obtain Fe 3 O 4 @SiO 2 @GMA-G@NH 2 ;
[0034] More preferably, the ethylenediamine mixed solution is a 40% ethylenediamine mixed solution, with isopropanol and ethanol as solvents;
[0035] More preferably, the dosage of the ethylenediamine mixed solution is 500 μL;
[0036] More preferably, the water bath reaction conditions are 80° C., 4 h;
[0037] Preferably, the phosphate group is modified to Fe by the following method: 3 O 4 @SiO 2 @GMA-G@NH 2 Surface: The Fe 3 O 4 @SiO 2 @GMA-G@NH 2 Add to POCl 3 and 2,4,6-trimethylpyridine in acetonitrile solution, react at room temperature for 1h to obtain Fe 3 O 4 @SiO 2@GMA-G@NH 2 @PO 3 ;
[0038] More preferably, the dosage of the acetonitrile solution is 500 μL;
[0039] More preferably, the acetonitrile solution contains POCl 3 The concentration is 40mM;
[0040] More preferably, the concentration of 2,4,6-trimethylpyridine in the acetonitrile solution is 40 mM;
[0041] Preferably, Ti is treated by the following method: 4+ Fixed on Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 Upper: The Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 Resuspend in Ti(SO 4 ) 2 Solution, react at room temperature for 1h to obtain Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ ;
[0042] More preferably, the Ti(SO 4 ) 2 The dosage is 0.1M, 1mL.
[0043] In the present invention, the principle of the preparation method is as follows: First, Fe 3 O 4 . FeCl 3 6H 2 O and anhydrous sodium acetate were mixed and suspended in ethylene glycol, and then subjected to solvothermal reaction at 220 °C. During the reaction, FeCl 3 6H 2 O iron salt is oxidized to Fe 3 O 4 , and precipitate, the obtained particles are washed three times with anhydrous ethanol and water in turn, and the precipitate is dried by heat. The silica layer is coated on the surface of the nanoparticles by the sol-gel method: Fe 3 O 4The particles were dispersed in a mixture of ethanol, water and concentrated ammonia, and then silanized by adding tetraethyl orthosilicate (Fe 3 O 4 @SiO 2 ). The SI-ATRP initiator is then fixed to the Fe by covalent bonding between the silane coupling agent and the silanol group. 3 O 4 Nanomaterials (Fe 3 O 4 @SiO 2 ) surface. Subsequently, the synthesized dextran compound 2-methacrylate 3-glucose aminopropyl ester (GMA-G) was used as a hydrophilic monomer, cuprous chloride was used as a catalyst, and 1,1,4,7,7-pentamethyldiethylenetriamine was used as a ligand (according to a molar ratio of 100:1:1.5) to react with the Fe 3 O 4 The nanomaterials are mixed evenly, initiating SI-ATRP reaction to modify GMA-G to Fe 3 O 4 Surface. The magnetic nanomaterials wrapped with dextran hydrophilic polymers were recovered by magnetic separation and washed three times with organic solvents and water to remove residual reactants. Subsequently, an oxidant was used to convert the diol on the GMA-G side chain on the surface of the magnetic nanomaterial into aldehyde. The oxidized poly-GMA-G modified magnetic nanomaterial was washed with an organic solvent to remove the residual oxidant. Then, a mixed solution of ethylenediamine was added to react with the aldehyde on the side chain of the oxidized GMA-G to undergo a Schiff base reaction to modify the amino group on the surface of the magnetic nanomaterial. Subsequently, an organic solvent was used to wash to remove excess reactants. Phosphorus oxychloride was used to undergo a nucleophilic reaction with the amino group on the surface of the magnetic nanomaterial to convert PO 3 Finally, PO 3 Modified magnetic nanomaterials dispersed in Ti 4+ In solution, PO 3 The group will be with Ti 4+ A novel composite magnetic nanomaterial of dextran polymer grafted with phosphate modified by chelation was obtained. 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ .
[0044] In the present invention, the SI-ATRP (surface-initiated atom transfer radical polymerization) method refers to the surface-initiated atom transfer radical polymerization method, which is an effective method for obtaining controllable polymer brushes on the surface of materials. According to the object of membrane separation, different activation groups are introduced through the SI-ATRP method to "activate" the membrane surface, and separation membranes with new structures and properties can be designed.
[0045] The second aspect of the present invention provides a novel composite magnetic nanomaterial modified by grafting phosphate with a dextran polymer prepared by the method described in the first aspect of the present invention.
[0046] Furthermore, the novel composite magnetic nanomaterial modified by dextran polymer grafted with phosphate is Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ .
[0047] The third aspect of the present invention provides any of the following applications:
[0048] (1) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate according to the second aspect of the present invention in enriching and / or separating phosphorylated proteins and / or phosphorylated peptides in a mixture;
[0049] (2) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate according to the second aspect of the present invention in enriching and / or separating phosphorylated proteins and / or phosphorylated peptides in cells;
[0050] (3) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate as described in the second aspect of the present invention in enriching and / or separating phosphorylated proteins and / or phosphorylated peptides in FFPE samples;
[0051] (4) Application of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate as described in the second aspect of the present invention in enriching and / or separating phosphorylated peptides from α-casein cleaved peptides.
[0052] In some embodiments, when the composite magnetic nanomaterial modified by the above-mentioned glucan polymer grafted with phosphate provided by the present invention is used for phosphorylated peptide enrichment and / or separation, the following steps can be followed: the sample containing phosphorylated peptides and the composite magnetic nanomaterial modified by the glucan polymer grafted with phosphate are dissolved in a binding buffer solution and fully mixed, and the phosphorylated peptides are enriched at 37°C; then the magnetic nanomaterial is separated from the solution by a magnetic separation method; the magnetic nanomaterial solution is washed with a washing buffer solution at room temperature, and the washing is repeated 3 times to remove impurities such as non-phosphorylated peptides and salts in the sample. Finally, the phosphorylated peptides adsorbed by the magnetic nanomaterial are eluted with an elution buffer, and the obtained phosphorylated peptides are subjected to mass spectrometry analysis.
[0053] In some embodiments, when the composite magnetic nanomaterial modified with the glucan polymer grafted with phosphate provided by the present invention is used to enrich and / or separate the phosphorylated modified standard protein α-casein, the following steps can be followed: a sample containing phosphorylated peptides is treated with a binding buffer solution (acetonitrile / H 2 O / TFA = 80 / 15 / 5, v / v / v, containing 0.1 M lactic acid), mixed with the composite magnetic nanomaterial modified with dextran polymer grafted phosphate, and enriched at 37°C for 30 min. Afterwards, the magnetic nanomaterial was washed once with the binding buffer solution, and the magnetic nanomaterial was washed with two washing buffer solutions (Buffer 1, acetonitrile / H 2 O / TFA=80 / 49 / 1; Buffer 2, acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2) to remove the acidic non-phosphorylated peptides adsorbed on the surface of the material. Finally, the eluent (10% NH 3 ·H 2 O) The phosphopeptides captured by the magnetic nanomaterials are eluted. Finally, the eluted solution is analyzed using matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. After enrichment, non-phosphorylated peptides and other impurities in the sample are basically removed, and the mass spectrometry signal intensity, signal-to-noise ratio, and identification number of phosphorylated peptides are significantly improved.
[0054] In some embodiments, when the composite magnetic nanomaterial modified with the glucan polymer grafted with phosphate provided by the present invention is used to enrich and / or separate a mixture of phosphorylated modified standard protein α-casein and bovine serum albumin, the following steps can be followed: a sample containing phosphorylated peptides is treated with a binding buffer solution (acetonitrile / H 2O / TFA = 80 / 15 / 5, v / v / v, containing 0.1 M lactic acid), mixed with the composite magnetic nanomaterial modified with dextran polymer grafted phosphate, and enriched at 37°C for 30 min. Afterwards, the magnetic nanomaterial was washed once with the binding buffer solution, and the magnetic nanomaterial was washed with two washing buffer solutions (Buffer 1, acetonitrile / H 2 O / TFA=80 / 49 / 1; Buffer 2, acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2) to remove the acidic non-phosphorylated peptides adsorbed on the surface of the material. Finally, the eluent (10% NH 3 ·H 2 O) The phosphopeptides captured by the magnetic nanomaterials are eluted. Finally, the eluted solution is analyzed using matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. After enrichment, non-phosphorylated peptides and other impurities in the sample are basically removed, and the mass spectrometry signal intensity, signal-to-noise ratio, and identification number of phosphorylated peptides are significantly improved.
[0055] In some embodiments, when the composite magnetic nanomaterial modified with the glucan polymer grafted with phosphate provided by the present invention is used to enrich and / or separate cell enzymatic digests, the following steps can be followed: a sample containing phosphorylated peptides is treated with a binding buffer solution (acetonitrile / H 2 O / TFA = 80 / 15 / 5, v / v / v, containing 0.1 M lactic acid), mixed with the composite magnetic nanomaterial modified with dextran polymer grafted phosphate, and enriched at 37°C for 30 min. Afterwards, the magnetic nanomaterial was washed once with the binding buffer solution, and the magnetic nanomaterial was washed with two washing buffer solutions (Buffer 1, acetonitrile / H 2 O / TFA=80 / 49 / 1; Buffer 2, acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2 to remove the acidic non-phosphorylated peptides adsorbed on the surface of the material. 3 ·H 2 O) eluting the phosphopeptides captured by the magnetic nanomaterial. Finally, the product is analyzed by liquid chromatography-mass spectrometry. Most of the non-phosphorylated peptides and other impurities in the enriched sample are removed, and the enrichment selectivity of phosphorylated peptides can reach 90.0%.
[0056] In a specific embodiment of the present invention, the composite magnetic nanomaterial modified by the above-mentioned glucan polymer grafted with phosphate was used to independently enrich 200 μg of HeLa cell digests three times, and 3,000 phosphoproteins and more than 13,000 phosphorylated peptides were successfully identified. 81.3% of the phosphorylated proteins were repeatedly identified 2 or more times, and 70.2% of the phosphorylated peptides were repeatedly identified 2 or more times, proving that the composite magnetic nanomaterial modified by the glucan polymer grafted with phosphate prepared by the present invention has good stability and repeatability, and can show good enrichment effect in the enrichment of phosphorylated peptides in actual biological samples.
[0057] In some embodiments, when the composite magnetic nanomaterial modified with the dextran polymer grafted with phosphate provided by the present invention is used to enrich and / or separate FFPE tissue, the following steps can be followed: a sample containing phosphorylated peptides is treated with a binding buffer solution (acetonitrile / H 2 O / TFA = 80 / 15 / 5, v / v / v, containing 0.1 M lactic acid) and mixed with the composite magnetic nanomaterial modified with dextran polymer grafted phosphate, and enriched at 37°C for 30 min. Afterwards, the magnetic nanomaterial was washed once with binding buffer and washed with two washing buffer solutions (Buffer 1, acetonitrile / H 2 O / TFA=80 / 49 / 1; Buffer 2, acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2 to remove the acidic non-phosphorylated peptides adsorbed on the surface of the material. 3 ·H 2 O) eluting the phosphopeptide captured by the magnetic nanomaterial. Finally, the product is analyzed by liquid chromatography-mass spectrometry.
[0058] In a specific embodiment of the present invention, when the above-mentioned composite magnetic nanomaterial modified by dextran polymer grafted with phosphate was used to enrich 50 μg of rat subcutaneous melanoma FFPE tissue, 1042 phosphorylated proteins and 3866 phosphorylated peptides were identified. 79.0% of the phosphorylated proteins were repeatedly identified 2 times or more, and 85.3% of the phosphorylated peptides were repeatedly identified 2 times or more, proving that the composite magnetic nanomaterial modified by dextran polymer grafted with phosphate prepared by the present invention showed good enrichment effect in the enrichment of phosphorylated peptides in actual biological samples.
[0059] In some embodiments, the cells include any cells that have the need to enrich and / or separate phosphorylated proteins and / or phosphorylated peptides therein. Exemplarily, the cells include but are not limited to: HeLa cells, cells of any animal origin, and cells of any plant origin.
[0060] In some embodiments, the animals include but are not limited to mammals (humans and non-human animals), including but not limited to humans, non-human primates (particularly higher primates, such as macaques, crab-eating macaques, short-tailed macaques, bear monkeys, flat-topped monkeys, golden monkeys and tree shrews), sheep, dogs, rodents (such as mice or rats), guinea pigs, goats, pigs, cats, rabbits, cows, any livestock or pets, etc.
[0061] In some embodiments, the FFPE sample refers to any formalin-fixed paraffin-embedded sample that has a requirement for enriching and / or isolating phosphorylated proteins and / or phosphorylated peptides therein, and the FFPE sample preparation technique involves placing cells or tissues in a formalin fixative, and then storing the fixed cells or tissues in paraffin. In a specific embodiment of the present invention, the FFPE sample is a rat subcutaneous melanoma FFPE tissue.
[0062] In a specific embodiment of the present invention, the present invention successfully achieves the enrichment and separation of phosphorylated peptides in complex samples such as standard phosphorylated proteins, HeLa cells and rat subcutaneous melanoma FFPE tissues by using the novel composite magnetic nanomaterials modified by dextran polymer grafting phosphate. The selective enrichment and separation effects are obvious. A total of 13,549 phosphorylated peptides were enriched and identified in the HeLa cell peptide segment, corresponding to 3,565 phosphorylated proteins; 3,866 phosphorylated peptides were identified in the rat subcutaneous melanoma FFPE tissue peptide segment, corresponding to 1,042 phosphorylated proteins.
[0063] The fourth aspect of the present invention provides a method for enriching and / or separating phosphorylated peptides from α-casein cleaved peptides.
[0064] Furthermore, the method comprises the following steps: dissolving the α-casein cleavage peptide and the novel composite magnetic nanomaterial modified with glucan polymer grafted with phosphate described in the second aspect of the present invention in a binding buffer solution and mixing, and incubating at 37° C. to achieve enrichment of the α-casein cleavage peptide; washing the enriched composite magnetic nanomaterial with two washing buffer solutions, Buffer 1 and Buffer 2, respectively, and eluting the phosphorylated peptide on the composite magnetic nanomaterial with an elution buffer solution to achieve separation of the α-casein cleavage peptide;
[0065] Preferably, the dosage of the novel composite magnetic nanomaterial modified by glucan polymer grafted phosphate is 100 μg;
[0066] Preferably, the binding buffer solution is: acetonitrile / H 2 O / TFA = 80 / 15 / 5, v / v / v, containing 0.1 M lactic acid;
[0067] Preferably, the washing buffer solution Buffer 1 is: acetonitrile / H 2 O / TFA=80 / 49 / 1, v / v / v;
[0068] Preferably, the washing buffer solution Buffer 2 is: acetonitrile / H 2 O / TFA=10 / 89.8 / 0.2, v / v / v;
[0069] Preferably, the elution buffer solution is: 10% NH 3 ·H 2 O;
[0070] Preferably, the enrichment time is 30 min.
[0071] Compared with the prior art, the present invention has the following beneficial effects:
[0072] (1) The novel composite magnetic nanomaterial (Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ ) is a linear polymer obtained by surface atom transfer radical polymerization, with a large number of modifiable sites. After functional modification, it can carry a large amount of Ti 4+ A novel composite magnetic nanomaterial of dextran polymer grafted with phosphate modified with a highly rough surface and a high specific surface area;
[0073] (2) Compared with conventional materials bonded with a single layer of hydrophilic compounds, the polymer covered on the surface of the novel composite magnetic nanomaterial modified by grafted phosphate with a glucan polymer provided by the present invention carries a large number of hydrophilic functional groups and can form stable metal chelating sites, which effectively improves its hydrophilicity and the loading capacity of phosphorylated peptides; at the same time, the surface of the hydrophilic filler is composed of glucan monomers, which has both the strong polarity and hydrophilicity of carbohydrate substances. When enriching phosphorylated peptides, there are metal ion-phosphate group interactions and hydrophilic interactions between the magnetic nanomaterial and the material to be enriched, which makes it have a stronger and more extensive affinity for phosphorylated peptides, thereby effectively improving the efficiency and selectivity of enrichment;
[0074] (3) The novel composite magnetic nanomaterial modified by dextran polymer grafted with phosphate provided by the present invention is particularly suitable for enriching and separating phosphorylated peptides from trace complex samples. When the magnetic nanomaterial is used to enrich low-content phosphorylated peptides in complex samples, the selective enrichment effect is obvious, which greatly increases the number of identified phosphorylated peptides. In addition, the present invention proves through comparative experiments that the enrichment efficiency and enrichment specificity of the novel composite magnetic nanomaterial modified by dextran polymer grafted with phosphate are significantly better than those of magnetic nanomaterials prepared by other substances with similar effects and commercial phosphorylated peptide enrichment materials TiO 2 , which can increase the identification scale of phosphorylated proteins and phosphorylated peptides by 50% respectively;
[0075] (4) The novel composite magnetic nanomaterial modified by dextran polymer grafted phosphate provided by the present invention adopts magnetic Fe 3 O 4 As the base material, it has strong paramagnetism. Therefore, the composite magnetic nanomaterial can be used for solid-liquid separation using a magnetic suction device, which is simple and convenient to operate; and can be used for automated high-throughput enrichment experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 : Flow chart of the technical solution of the present invention.
[0077] Figure 2 : Scanning electron microscopy results, where (a) is the magnetic Fe without dextran modification 3 O 4 Scanning electron microscope image of (b) magnetic nanomaterials grafted with dextran polymer (Fe 3 O 4 @SiO 2 @GMA-G); (c) is a new type of composite magnetic nanomaterial (Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ ) of the scanning electron microscope.
[0078] Figure 3 : EDS elemental spectrum of the novel composite magnetic nanomaterial modified by dextran polymer grafted phosphate, wherein (a) is C; (b) is N; (c) is P; and (d) is Ti.
[0079] Figure 4: Thermogravimetric analysis, hysteresis characteristics analysis and Zeta potential analysis result diagrams, wherein, (a) is the thermogravimetric analysis curve of the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate at different modification stages; (b) is the hysteresis curve analysis of the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate at different modification stages; (c) is the Zeta potential analysis of the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate at different modification stages. Figure 5 : Water contact angle measurement diagram of novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate at different modification stages, where (a) is the magnetic Fe without dextran modification 3 O 4 ; (b) is a magnetic nanomaterial grafted with a dextran polymer; (c) is a novel composite magnetic nanomaterial modified with a dextran polymer grafted with a phosphate provided by the present invention. Figure 6 : MALDI-TOF-MS mass spectrometry result diagram, wherein (a) is the MALDI-TOF-MS mass spectrometry diagram of the peptides of α-casein after trypsin hydrolysis without enrichment; (b) is the MALDI-TOF-MS mass spectrometry diagram of the peptides of α-casein after trypsin hydrolysis, after enrichment using the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate provided by the present invention.
[0080] Figure 7 : MALDI-TOF-MS mass spectrometry result diagram, wherein (a) is a MALDI-TOF-MS mass spectrum diagram of peptides of a mixture of α-casein and bovine serum albumin (molar ratio 1:100) without enrichment after trypsin hydrolysis; (b) is a MALDI-TOF-MS mass spectrum diagram of peptides of a mixture of α-casein and bovine serum albumin (molar ratio 1:100) after trypsin hydrolysis, enriched using the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate provided by the present invention; (c) is a MALDI-TOF-MS mass spectrum diagram of peptides of a mixture of α-casein and bovine serum albumin (molar ratio 1:1000) after trypsin hydrolysis, enriched using the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate provided by the present invention.
[0081] Figure 8 : The identification result diagram after enrichment of HeLa cell trypsin-cleaved peptides using the novel composite magnetic nanomaterial modified with dextran polymer grafted phosphate provided by the present invention and analysis by liquid chromatography-mass spectrometry, wherein (a) is the analysis of phosphorylated proteins, phosphorylated peptides and phosphorylation sites; (b) is the evaluation of the enrichment efficiency of phosphorylated peptides; (c) is the Venn diagram of phosphorylated proteins; and (d) is the Venn diagram of phosphorylated peptides.
[0082] Fig. 9 : Comparison of the enrichment and identification results of phosphorylated peptides by the novel composite magnetic nanomaterials modified with dextran polymer grafted phosphate and glycidyl methacrylate modified magnetic nanomaterials and commercial dextran magnetic beads provided by the present invention, wherein: (a) is a comparison of phosphorylated proteins, phosphorylated peptides and phosphorylation sites; (b) is a comparison of the enrichment efficiency of phosphorylated peptides; (c) is a Venn diagram of phosphorylated proteins; and (d) is a Venn diagram of phosphorylated peptides.
[0083] Fig.10 The present invention provides a novel composite magnetic nanomaterial of dextran polymer grafted with phosphate and a commercial phosphorylated peptide enrichment material TiO 2 Comparison of the results of phosphorylated peptide enrichment identification, where (a) is the comparison of phosphorylated proteins, phosphorylated peptides and phosphorylation sites; (b) is the comparison of phosphorylated peptide enrichment efficiency; (c) is the Venn diagram of phosphorylated proteins; (d) is the Venn diagram of phosphorylated peptides.
[0084] Fig.11 : The novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate provided by the present invention is used to enrich the trypsin-cleaved peptide fragments of rat subcutaneous melanoma tissue protein, and then the identification results after liquid chromatography-mass spectrometry analysis are analyzed, wherein (a) is a comparison of phosphorylated proteins, phosphorylated peptides and phosphorylation sites; (b) is a Venn diagram of phosphorylated proteins; and (c) is a Venn diagram of phosphorylated peptides. DETAILED DESCRIPTION
[0085] The present invention is further described below in conjunction with specific embodiments, which are only used to explain the present invention and cannot be understood as limiting the present invention. It can be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and purpose of the present invention, and the scope of the present invention is defined by the claims and their equivalents.
[0086] The reagents and raw materials used in the present invention are easily obtained by ordinary technicians in the field and can be obtained from commercial channels unless otherwise specified. The experimental methods in the present invention that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. In particular, the following examples are only used to illustrate the present invention and should not limit the scope of the present invention in any way.
[0087] Example 1 Preparation and performance characterization of novel composite magnetic nanomaterials modified by dextran polymer grafted with phosphate
[0088] The experimental process of preparing a novel composite magnetic nanomaterial modified by dextran polymer grafted with phosphate by SI-ATRP is as follows: Figure 1 shown.
[0089] (1) Synthesis of 2-methylacrylate 3-glucose aminopropyl ester (GMA-G) monomer: After the first oxidation reaction of glycidyl methacrylate with 0.2 M sulfuric acid at 50° C. for 4 hours, sodium periodate was added and the reaction was carried out at room temperature in the dark for 4 hours for the second oxidation.
[0090] 0.5 M glucosamine hydrochloride and 1% NaBH 3 CN is dissolved in 20 mL of methanol containing 1.1 g of NaOH. The product obtained by oxidation is mixed with a methanol solution of glucosamine and subjected to a Schiff base reaction at room temperature for 4-12 hours. The molar ratio of glycidyl methacrylate, sulfuric acid, sodium periodate, and glucosamine hydrochloride is 1:0.4:1:1. After the reaction is completed, the prepared solution is dried with nitrogen and evaporated to a paste state, at which time the hydrophilic monomer GMA-G is obtained, and the obtained GMA-G monomer is sealed and stored at 4°C.
[0091] (2) Synthesis of SI-ATRP initiator: A silane coupling agent 3-aminopropyltriethoxysilane was reacted with an ATRP initiator 2-bromoisobutyryl bromide to synthesize a SI-ATRP initiator having a silane coupling agent capable of bonding to the surface of a silica filler at one end and an ATRP initiator at the other end.
[0092] 3-Aminopropyltriethoxysilane (1.875mL, 8mmol) and triethylamine (1.4mL, 10mmol) were added to 12.5mL tetrahydrofuran. The mixed solution was deoxygenated with nitrogen and kept in an ice bath for 30 minutes. 2-Bromoisobutyryl bromide (1.25mL, 10mmol) was slowly added dropwise to the mixture and stirred vigorously for 4 hours. The solution was filtered and vacuum dried to 1 / 3 of the original volume to remove tetrahydrofuran and triethylamine. The precipitate was removed after centrifugation and dried with nitrogen. After drying, a yellow viscous liquid was obtained, and the obtained product (SI-ATRP initiator) was sealed and stored at 4°C.
[0093] (3) Magnetic Fe 3 O 4 Synthesis: Weigh 2.70 g FeCl 3 6H 2 O was dissolved in 100 mL of ethylene glycol, ultrasonicated for 5 min (until dissolved), and a yellow transparent liquid was obtained. 7.20 g of anhydrous sodium acetate was added, and mechanically stirred for 30 min at room temperature (stirred until dissolved). The obtained uniform solution was transferred to a 30 mL Teflon-lined stainless steel reactor, heated to 220 ° C, and reacted for 8 h. After the reaction was completed, the reactor was taken out and cooled to room temperature. The obtained particles were washed with anhydrous ethanol and water three times in turn, and the precipitate was dried at 60 ° C to obtain magnetic Fe 3 O 4 .
[0094] (4) Magnetic Fe 3 O 4 Silanization: The silicon dioxide layer is coated on the surface of magnetic nanomaterials by sol-gel method: 350 mg Fe 3 O 4 The particles were washed twice with ethanol, dispersed in a mixture of 160 mL ethanol, 40 mL water and 1.5 mL concentrated ammonia, and ultrasonicated for 30 min. 1.0 mL of ethyl orthosilicate was added dropwise, and mechanically stirred at 30 ° C for 6 h. Then magnetic separation was performed, and the particles were washed three times with water and ethanol, respectively, to obtain silanized magnetic Fe 3 O 4 (Fe 3 O 4 @SiO 2 ).
[0095] (5) Fixation of SI-ATRP initiator: Silane coupling agent on SI-ATRP initiator and magnetic Fe 3 O 4 The silanol groups on the surface undergo a dehydration reaction to generate covalent silicon-oxygen bonds, thereby fixing the SI-ATRP initiator on the surface of the silica gel filler.
[0096] Cleaning magnetic Fe with methanol 3 O 4 , and washed three times. Then, a methanol solution (500 μL) containing 500 μM SI-ATRP initiator was mixed with the washed silanized magnetic Fe 3 O 4 (Fe 3 O 4 @SiO 2 ) materials were mixed and dehydrated for 12 h at 37° C. After the reaction, the remaining initiator was removed and the obtained magnetic nanomaterial was washed with a methanol solution.
[0097] (6) Introducing a hydrophilic polymer monomer GMA-G to generate a poly-GMA-G copolymer chain on the surface of the magnetic nanomaterial: the monomer used is the above-synthesized GMA-G with a double bond at one end and glucose at the other end.
[0098] The hydrophilic monomer GMA-G, the catalyst cuprous chloride, and the ligand 1,1,4,7,7-pentamethyldiethylenetriamine were added to methanol in a molar ratio of 100:1:1.5, and ultrasonic treatment was performed to dissolve and mix them evenly. The above reaction solution was mixed with the magnetic nanomaterial with the SI-ATRP initiator fixed on the surface, sealed and stirred at 60°C for 3 hours. After the reaction was completed, the residual reactants were repeatedly washed with methanol to obtain the GMA-G copolymer modified magnetic nanomaterial (Fe 3 O 4 @SiO2 @GMA-G).
[0099] (7) Synthesis of novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate: using 10 mM NaIO 4 (500 μL) was used to convert the diol on the side chain of poly GMA-G into aldehyde. The oxidized poly GMA-G modified magnetic nanomaterial was washed with ethanol, mixed with 40% ethylenediamine (EDA) (500 μL) (50% isopropanol / ethanol V / V as solvent) mixed solution, and carried out in a water bath at 80 ° C for 4 hours. After the reaction was completed, the remaining reaction solution was washed with acetonitrile to obtain the ethylenediamine fixed magnetic nanomaterial Fe 3 O 4 @SiO 2 @GMA-G@NH 2 Take the magnetic nanomaterial fixed with ethylenediamine and add it to 500 μL of acetonitrile solution (containing 40 mM phosphorus oxychloride (POCl 3 ) and 40 mM 2,4,6-trimethylpyridine) and reacted at room temperature for 1 hour. After the reaction, the magnetic nanomaterial (Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 ), the magnetic nanomaterials were resuspended in 0.1 M Ti(SO 4 ) 2 (1 mL) solution and reacted at room temperature for 1 hour. After the reaction, the excess Ti was removed by washing with water and 200 mM NaCl. 4+ ions, and finally a novel composite magnetic nanomaterial (Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+ ).
[0100] Take the magnetic Fe prepared by the above method 3 O 4 , GMA-G modified magnetic nanomaterials (Fe 3 O 4 @SiO 2 @GMA-G) and dextran polymer grafted phosphate modified composite magnetic nanomaterials (Fe 3 O 4 @SiO 2 @GMA-G@NH 2 @PO 3 @Ti 4+) were analyzed by scanning electron microscopy, and the results are shown in Figure 2 .
[0101] Depend on Figure 2 It can be seen that magnetic Fe 3 O 4 The surface morphology of (a), magnetic nanomaterial modified by GMA-G (b) and composite magnetic nanomaterial modified by dextran polymer grafted phosphate (c) is obviously different. The surface of composite magnetic nanomaterial modified by dextran polymer grafted phosphate is highly rough. It proves that the surface modification of magnetic nanomaterial by GMA-G by SI-ATRP method is successful.
[0102] The new composite magnetic nanomaterials modified by dextran polymer grafted with phosphate were analyzed by EDS. Figure 3 .
[0103] Depend on Figure 3 It can be seen that the signals of elements such as C, N, P, and Ti exist simultaneously in the same area, further confirming the successful synthesis of the new type of composite magnetic nanomaterials modified by dextran polymer grafted phosphate.
[0104] 100 mg of magnetic nanomaterials at different modification stages and unmodified magnetic nanomaterials were weighed respectively for thermogravimetric analysis, hysteresis curve analysis and Zeta potential analysis. The results are shown in Figure 4 .
[0105] The novel composite magnetic nanomaterials modified by dextran polymer grafted with phosphate consist of a polymer layer that can be thermally decomposed to cause mass loss and a magnetic Fe 3 O 4 It consists of two parts. Figure 4 As can be seen in (a), the magnetic nanomaterials without modification of GMA-G have no obvious mass loss with the increase of heat treatment temperature. However, the composite magnetic nanomaterials modified by the new dextran polymer grafted phosphate show obvious mass loss in the range of 200-800°C, and the mass loss can reach 20%. This proves that the new composite magnetic nanomaterials modified by the dextran polymer grafted phosphate have been successfully synthesized.
[0106] The hysteresis loops of unmodified magnetic nanomaterials and magnetic nanomaterials at different modification stages were studied using a vibrating sample magnetometer. Figure 4 (b) It can be seen that the synthesized magnetic Fe 3 O 4 The saturation magnetization is 76.9emu g -1 , has strong paramagnetism. The saturation magnetization intensity of the synthesized new type of dextran polymer grafted phosphate modified composite magnetic nanomaterial is 52.1emu g -1, lower than the unmodified magnetic Fe 3 O 4 , which may be due to GMA-G@NH 2 @PO 3 @Ti 4+ The introduction of non-magnetic shell, but the new type of dextran polymer grafted phosphate modified composite magnetic nanomaterials still has strong superparamagnetism, which further confirms the successful synthesis of the new type of dextran polymer grafted phosphate modified composite magnetic nanomaterials. At the same time, it proves that the nanoparticles can be well dispersed in water / organic phase, and quickly respond to magnetic field, and can be easily and quickly separated from the solid-liquid system.
[0107] At the same time, Zeta potential analysis was used to monitor the surface potential changes of unmodified magnetic nanomaterials and magnetic nanomaterials at different modification stages. Figure 4 (c) It can be seen that the Zeta potential of the surface of the GMA-G modified magnetic nanomaterial is -12.8 mV, which is attributed to the magnetic Fe 3 O 4 The surface is heavily modified with dextran GMA-G, and there are a lot of hydroxyl groups on the side chains of GMA-G. 4+ When chelated on the surface of magnetic nanomaterials, the Zeta potential increased to +6.4 mV. The change in Zeta potential indicates that a new type of composite magnetic nanomaterial modified by dextran polymer grafted with phosphate has been successfully synthesized based on electrostatic interaction.
[0108] Weigh 100 mg of magnetic nanomaterials at different modification stages and unmodified magnetic nanomaterials respectively, and perform hydrophilic contact angle analysis. The results are shown in Figure 5 .
[0109] Depend on Figure 5 It can be seen that the magnetic Fe 3 O 4 The contact angle is 52.87° when the magnetic Fe 3 O 4 After the surface was modified with the hydrophilic monomer GMA-G, the magnetic material became significantly hydrophilic, and the contact angle became 25.10°. This is because the hydroxyl groups on the side chains of GMA-G increased the hydrophilicity of the magnetic material. After the GMA-G-modified magnetic nanomaterial was modified with various amino and phosphate groups, the contact angle of the magnetic material became 15.69°. This is because a large number of amino and phosphate groups were modified on the surface of the magnetic nanoparticles, and the amino and phosphate groups can form hydrogen bonds with water molecules, increasing the hydrophilicity of the magnetic nanomaterial. Example 2: Enrichment of phosphorylated peptides in α-casein using the new type of glucan polymer grafted phosphate-modified composite magnetic nanomaterial obtained in Example 1
[0110] (1) Take an appropriate amount of α-casein and dissolve it in 50 mM NH 4 HCO 3 The protein concentration was 1 mg mL -1 Trypsin (trypsin concentration 0.5 mg mL) was added at a mass ratio of 1:50 (trypsin: protein). -1 ). The mixture was incubated at 37°C for 18 hours. After the incubation, the digestion solution was concentrated, packaged, and heat-dried. The heat-dried peptides were stored at -80°C.
[0111] (2) 100 μg of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate prepared in Example 1 was mixed with acetonitrile / H 2 The plate was washed three times with O / TFA (80 / 15 / 5, v / v / v, containing 0.1 M lactic acid).
[0112] (3) The α-casein peptide obtained in step (1) was washed with loading buffer (acetonitrile / H 2 O / TFA=80 / 15 / 5, v / v / v, containing 0.1M lactic acid) and added the peptide mixture solution to the washed 100μg novel composite magnetic nanomaterials modified with dextran polymer grafted phosphate and incubated at 37℃ for 30 minutes. After the enrichment, the novel composite magnetic nanomaterials modified with dextran polymer grafted phosphate were washed with two buffer washing solutions (Buffer 1, acetonitrile / H 2 O / TFA=80 / 49 / 1; Buffer 2, acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2 to remove the acidic non-phosphorylated peptides adsorbed on the surface of the material. After washing, use eluent (10% NH 3 ·H 2 O) The phosphopeptides captured by the magnetic nanomaterials are eluted. Finally, the eluted solution is analyzed using a matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) system.
[0113] 1 μL of the α-casein peptide fragments without enrichment and enriched with the novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate were respectively spotted on the target of matrix-assisted laser desorption ionization time-of-flight mass spectrometer. After drying, DHB (DHB, 25 mg / mL, ACN / H 2 O / H 3 PO 4 =70:29:1, v / v / v) as the matrix, and mass spectrometry analysis was performed after the solution on the target crystallized. The results are shown in the figure Figure 6Table 1 shows the molecular weight and peptide sequence of phosphorylated peptides in α-casein enriched by the novel composite magnetic nanomaterials modified by dextran polymer grafted with phosphate.
[0114] Depend on Figure 6 (a) It can be seen that before the enrichment process, MALDI-TOF only detected three low-intensity phosphorylated peptides from the trypsin digest of α-casein. This is because the high-intensity non-phosphorylated peptide signals seriously interfered with the phosphorylated peptide signals. Figure 6 (b) It can be seen that after enrichment by the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate, the non-phosphorylated peptides were significantly removed, and the number of identified phosphopeptides and the signal intensity were significantly increased. This indicates that the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate has a high enrichment ability for phosphopeptides in the standard protein α-casein.
[0115] Table 1 Molecular weight and peptide sequence of phosphorylated peptides in α-casein enriched by novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate
[0116]
[0117]
[0118] Wherein, [pS]: phosphorylated serine; [Mo]: oxidation on methionine; Q*: pyroglutamylation on N-terminal Gln.
[0119] Example 3 Enrichment of phosphorylated peptides in a mixed sample using the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate obtained in Example 1
[0120] (1) Take an appropriate amount of α-casein and dissolve it in 50 mM NH 4 HCO 3 The protein concentration was 1 mg mL -1 Trypsin (trypsin concentration 0.5 mg mL) was added at a mass ratio of 1:50 (trypsin: protein). -1 ). The mixture was incubated at 37°C for 18 hours. After the incubation, the digestion solution was concentrated, packaged, and heat-dried. The heat-dried peptides were stored at -80°C.
[0121] (2) Take an appropriate amount of BSA and dissolve it in 1 mL of 8.0 M UA (containing 0.1 M Tris-HCl) denaturing solution, add 0.1 M DTT to make the final concentration 20 mM, and incubate the resulting mixture at 37°C for 4 hours. After the incubation, add 0.1 M CAA to make the final concentration 40 mM, and alkylate the mixed solution at room temperature for 40 minutes. After the alkylation is completed, use 50 mM NH4 HCO 3 The obtained mixture was diluted 8 times and trypsin was added (trypsin: protein = 1:50). The enzymatic cleavage mixture was incubated at 37°C for 18 hours. After the enzymatic cleavage, 10% TFA aqueous solution was added to adjust the pH of the mixture to about 2 to 3. Then, the mixture was desalted using an OASIS HLB3cc Vac column. The desalted peptide mixture was vacuum dried, then dissolved in 0.1% FA aqueous solution, the concentration was measured, and then aliquoted and heat-dried. The heat-dried peptide powder was stored at -80°C.
[0122] (3) Take 100 μg of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate prepared in Example 1 and acetonitrile / H 2 The plate was washed three times with O / TFA (80 / 15 / 5, v / v / v, containing 0.1 M lactic acid).
[0123] (4) The α-casein peptide fragments and BSA peptide fragments obtained in step (1) and step (2) were mixed (mass ratio 1:100) and washed with loading buffer (acetonitrile / H 2 O / TFA=80 / 15 / 5, v / v / v, containing 0.1M lactic acid) and added the peptide mixture solution to the washed 100μg novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate and incubated at 37℃ for 30 minutes. After the enrichment, the novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate were washed with two buffer washing solutions (Buffer 1, acetonitrile / H 2 O / TFA=80 / 49 / 1; Buffer 2, acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2 to remove the acidic non-phosphorylated peptides adsorbed on the surface of the material. After washing, use eluent (10% NH 3 ·H 2 O) The phosphopeptides captured by the magnetic nanomaterials were eluted. Finally, the eluted solution was analyzed using a matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) system. The results are shown in the figure below. Figure 7 shown.
[0124] Depend on Figure 7 (a) It can be seen that when the mixing ratio of α-casein and BSA is 1:100, no phosphorylated peptides are detected by MALDI-TOF without phosphorylated peptide enrichment. Figure 7(b) It can be seen that when the new composite magnetic nanomaterial modified with dextran polymer grafted with phosphate was used to enrich phosphorylated peptides, 20 standard phosphorylated peptides were detected by MALDI-TOF, which proved that the new composite magnetic nanomaterial modified with dextran polymer grafted with phosphate had good enrichment specificity. Figure 7 (c) It can be seen that when the amount of BSA is increased to 1000 times that of α-casein, the novel composite magnetic nanomaterial modified by dextran polymer grafted phosphate can still successfully enrich 5 phosphopeptides from a complex mixture, and the phosphopeptide signal is less interfered by the non-phosphopeptide signal. The results show that the novel composite magnetic nanomaterial modified by dextran polymer grafted phosphate synthesized by the present invention has the ability to enrich phosphorylated peptides under a strong interference background.
[0125] Example 4 Enrichment of phosphorylated peptides in HeLa cell samples using the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate obtained in Example 1
[0126] (1) Take 400 μg of HeLa cell whole protein in a 30KD ultrafiltration tube. Add 0.1M DTT to the sample to make the final concentration of 20mM DTT, and incubate at 37°C for 4h, then centrifuge to remove the centrifuge solution. Add 200μL 40mM CAA and react at room temperature for 40min. After the reaction, wash 3 times with 200μL 50mM ABC. Finally, add 8μg trypsin and incubate at 37°C for 18h. After overnight enzymatic digestion, wash the peptide fragments in the ultrafiltration tube with ultrapure water, and use a freeze dryer to dry the peptide solution. Finally, store the peptide sample obtained after enzymatic digestion in a -80°C refrigerator.
[0127] (2) 100 μg of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate prepared in Example 1 was mixed with acetonitrile / H 2 The plate was washed three times with O / TFA (80 / 15 / 5, v / v / v, containing 0.1 M lactic acid).
[0128] (3) The HeLa cell cleavage peptide obtained in step (1) was washed with 100 μL Binding Buffer (acetonitrile / H 2O / TFA=80 / 15 / 5, v / v / v, containing 0.1M lactic acid). Add the Binding Buffer containing the HeLa cell cleaved peptide fragments to the washed novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate. Incubate the mixture at 37°C for 30min using an oscillator. After the reaction, place the sample on a magnetic stand, let it stand for 1min, remove the supernatant, and wash the bound magnetic nanomaterials with 200μL Binding Buffer. The washing process is mixed and shaken on the oscillator for 5min; then continue to use 200μL Washing Buffer 1 (acetonitrile / H 2 O / TFA=80 / 49 / 1,v / v / v) and Washing Buffer 2 (acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2, v / v / v). After washing, use 200 μL Elution Buffer (10% NH 3 ·H 2 O) The phosphopeptides captured by the magnetic nanomaterials were eluted twice, and the eluted phosphopeptides were dried at 45°C. Finally, liquid chromatography-mass spectrometry was used for monitoring and analysis. Figure 8 shown.
[0129] It can be seen from the analysis chart and Venn diagram of the results of three repeated identifications that the new composite magnetic nanomaterial modified by the glucan polymer grafted phosphate has strong enrichment selectivity and enrichment efficiency. In the three repeated experiments, 13,549 phosphorylated peptides were enriched and identified, corresponding to 3,563 phosphorylated proteins, and the enrichment efficiency reached 90%. Among them, 70.2% and 81.3% of the phosphorylated peptides and phosphorylated proteins were repeatedly identified in at least two experiments, which fully demonstrates that the above-mentioned new composite magnetic nanomaterial modified by the glucan polymer grafted phosphate has good enrichment reproducibility. After comparing the new composite magnetic nanomaterial modified by the glucan polymer grafted phosphate provided by the present invention with the magnetic nanomaterial modified by the non-hydrophilic compound methacrylate glycidyl ester and the commercial glucan amino magnetic beads, it was found that the new composite magnetic nanomaterial modified by the glucan polymer grafted phosphate provided by the present invention not only enriches more phosphorylated proteins and phosphorylated peptides, but also has a higher enrichment efficiency ( Fig. 9 ). It is proved that the effect of the magnetic nanomaterial prepared by using the GMA-G of the present invention is significantly better than that of the magnetic nanomaterial prepared by using other substances with similar effects. 2 After comparison, it was found that the new composite magnetic nanomaterials modified with dextran polymer grafted with phosphate not only had significantly higher enrichment efficiency, but also increased the identification scale of phosphorylated proteins and phosphorylated peptides by 50% ( Fig.10In addition to the enrichment specificity, the novel dextran polymer grafted phosphate-modified composite magnetic nanomaterials additionally enriched 45.5% of phosphopeptides and 30.4% of phosphoproteins, while TiO 2 Only additional enrichments of 14.7% and 8.0% were achieved.
[0130] Example 5 Enrichment of phosphorylated peptides in rat subcutaneous melanoma FFPE samples using the novel dextran polymer grafted phosphate-modified composite magnetic nanomaterial obtained in Example 1
[0131] (1) Take 10 mg of rat subcutaneous melanoma FFPE sample in 100 μL guanidine hydrochloride lysis buffer, grind in a grinder, set the grinder parameters (one program): 4°C, rotation 50s, hold 60s, 12 cycles, centrifugation at 6000rpm for 1min; put the tissue grinding tube into the grinder, balance it, and run the set program (the specific number of grinding programs needs to be determined according to the actual grinding conditions). After grinding, incubate at 95°C for 2h. Centrifuge the grinding tube at high speed for 5min, transfer the supernatant to a new 1.5mL centrifuge tube, and record the volume; add half the volume of the above lysis buffer to the precipitate and grind again for 6 cycles. After grinding, centrifuge at high speed for 5min, transfer the supernatant to the corresponding 1.5mL centrifuge tube, and record the volume. Then use the BCA protein assay kit to measure its protein concentration. Add 5μL 1M DTT to the sample for reduction, shake and mix, and react at room temperature for 60min. Then, 20 μL 1M CAA was added to the sample, shaken and mixed, and alkylated at room temperature in the dark for 60 min. Finally, 10 μL 1M DTT was added to the sample to a final concentration of 20 mM, and quenched at room temperature for 30 min. SP3 enzyme digestion method was used to extract peptides from rat FFPE tissue.
[0132] (2) 100 μg of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate prepared in Example 1 was mixed with acetonitrile / H 2 The plate was washed three times with O / TFA (80 / 15 / 5, v / v / v, containing 0.1 M lactic acid).
[0133] (3) The rat subcutaneous melanoma FFPE sample cleavage peptide fragments obtained in step (1) were mixed with 100 μL Binding Buffer (acetonitrile / H 2O / TFA = 80 / 15 / 5, v / v / v, containing 0.1M lactic acid). Add the Binding Buffer containing the enzymatic peptide fragments of rat subcutaneous melanoma FFPE samples to the washed novel composite magnetic nanomaterials modified with dextran polymer grafted with phosphate. Incubate the mixture at 37°C for 30 minutes using an oscillator. After the reaction, place the sample on a magnetic stand, let it stand for 1 minute, remove the supernatant, and wash the bound magnetic nanomaterials with 200μL Binding Buffer. The washing process is mixed and shaken on the oscillator for 5 minutes; then continue to use 200μL Washing Buffer 1 (acetonitrile / H 2 O / TFA=80 / 49 / 1,v / v / v) and Washing Buffer 2 (acetonitrile / H 2 O / TFA = 10 / 89.8 / 0.2, v / v / v). After washing, use 200 μL Elution Buffer (10% NH 3 ·H 2 O) Elute the phosphopeptides captured by the magnetic nanomaterials twice, and heat dry the eluted phosphopeptides at 45°C. Finally, liquid chromatography-mass spectrometry is used for monitoring and analysis. The results are shown in the figure below. Fig.11 shown.
[0134] It can be seen from the analysis chart and Venn diagram of the three repeated identification results that the novel composite magnetic nanomaterial modified by dextran polymer grafted phosphate prepared by the present invention has a strong enrichment effect. 3866 phosphorylated peptides were enriched and identified in three repeated experiments, corresponding to 1042 phosphorylated proteins. Among them, 82.9% and 76.7% of the phosphorylated peptides and phosphorylated proteins were repeatedly identified in at least two experiments, which fully demonstrates that the novel composite magnetic nanomaterial modified by dextran polymer grafted phosphate has good enrichment reproducibility in actual biological samples.
Claims
1. A method for preparing a novel composite magnetic nanomaterial modified by glucan polymer grafted with phosphate, characterized in that: The method comprises the following steps: using 2-methylacrylate 3-glucose aminopropyl ester GMA-G as a polymerization monomer, cuprous chloride as a catalyst, and 1,1,4,7,7-pentamethyldiethylenetriamine as a ligand, after fixing the SI-ATRP initiator on the surface of Fe3O4@SiO2, introducing GMA-G, initiating SI-ATRP reaction on the surface of Fe3O4@SiO2 to generate Fe3O4@SiO2@GMA-G, chemically modifying the aldehyde group, amino group, and phosphoric acid group on the surface of Fe3O4@SiO2@GMA-G in sequence, and fixing Ti on the phosphoric acid group. 4+ A novel composite magnetic nanomaterial Fe3O4@SiO2@GMA-G@NH2@PO3@Ti was obtained by grafting phosphate-modified dextran polymer. 4 + ; The feeding molar ratio of the polymerization monomer, the catalyst and the ligand is 100-400:1:1-3; The SI-ATRP reaction is carried out in an organic solvent.
2. The method according to claim 1, characterized in that The feeding molar ratio of the polymerization monomer, the catalyst and the ligand is 100:1:1.
5.
3. The method according to claim 1, characterized in that: The organic solvent is methanol.
4. The method according to claim 1, characterized in that The reaction conditions of the SI-ATRP reaction were 60° C. and stirring for 3 h.
5. The method according to claim 1, characterized in that The GMA-G is prepared by the following method: glycidyl methacrylate is subjected to a first oxidation reaction with 0.2M sulfuric acid at 50°C for 4 hours, sodium periodate is added, and the reaction is carried out at room temperature in the dark for 4 hours for a second oxidation reaction, 0.5M glucosamine hydrochloride and 1% NaBH3CN are dissolved in methanol containing NaOH, the oxidation product is mixed with a methanol solution of glucosamine, and a Schiff base reaction is carried out at room temperature for 4-12 hours to obtain GMA-G.
6. The method according to claim 5, characterized in that The molar ratio of glycidyl methacrylate, sulfuric acid, sodium periodate and glucosamine hydrochloride is 1:0.25-1:0.5-2:0.5-2.
7. The method according to claim 6, characterized in that The molar ratio of glycidyl methacrylate, sulfuric acid, sodium periodate and glucosamine hydrochloride is 1:0.4:1:
1.
8. The method according to claim 1, characterized in that: The SI-ATRP initiator is prepared by the following method: 3-aminopropyltriethoxysilane and triethylamine are added to tetrahydrofuran, the mixed solution is deoxygenated with nitrogen and kept reacting in an ice bath for 30 minutes, 2-bromoisobutyryl bromide is slowly added dropwise to the mixed solution and vigorously stirred for 4 hours to obtain the SI-ATRP initiator.
9. The method according to claim 8, characterized in that The dosage of the 3-aminopropyltriethoxysilane is 1.875 mL, 8 mmol.
10. The method according to claim 8, characterized in that The dosage of the triethylamine is 1.4 mL, 10 mmol.
11. The method according to claim 8, characterized in that The dosage of the tetrahydrofuran is 12.5 mL.
12. The method according to claim 8, characterized in that The dosage of the 2-bromoisobutyryl bromide is 1.25 mL, 10 mmol.
13. The method according to claim 1, characterized in that The Fe3O4@SiO2 is prepared by the following method: dissolving FeCl3·6H2O in ethylene glycol, ultrasonically dissolving, adding anhydrous sodium acetate, and after dissolution, reacting the obtained uniform solution at 220° C. for 8 hours to obtain Fe3O4, dispersing Fe3O4 in a mixed solution of ethanol, water and concentrated ammonia water, adding tetraethyl orthosilicate, and stirring at 30° C. for 6 hours to obtain Fe3O4@SiO2.
14. The method according to claim 13, characterized in that The dosage of the FeCl3·6H2O is 2.70 g.
15. The method according to claim 13, characterized in that The dosage of the ethylene glycol is 100 mL.
16. The method according to claim 13, characterized in that The dosage of the anhydrous sodium acetate is 7.20 g.
17. The method according to claim 13, characterized in that The dosage of Fe3O4 is 350 mg.
18. The method according to claim 13, characterized in that The dosages of the ethanol, water and concentrated ammonia water are 160 mL, 40 mL and 1.5 mL respectively.
19. The method according to claim 13, characterized in that The dosage of the tetraethyl orthosilicate is 1.0 mL.
20. The method according to claim 1, characterized in that Fixing the SI-ATRP initiator on the surface of Fe3O4@SiO2 comprises the following steps: uniformly mixing the Fe3O4@SiO2 described in claim 5 with a methanol solution containing the SI-ATRP initiator, and subjecting the mixture to a dehydration reaction for 12 hours.
21. The method according to claim 20, characterized in that The SI-ATRP initiator was used at a dosage of 500 μM.
22. The method according to claim 20, characterized in that The dosage of the methanol is 500 μL.
23. The method according to claim 20, characterized in that The dehydration reaction was carried out at 37°C.
24. The method according to claim 1, characterized in that The aldehyde group was modified on the surface of Fe3O4@SiO2@GMA-G by the following method: NaIO4 was reacted with the Fe3O4@SiO2@GMA-G to obtain the aldehyde group-modified Fe3O4@SiO2@GMA-G.
25. The method according to claim 24, characterized in that The dosage of NaIO4 used is 10 mM, 500 μL.
26. The method according to claim 24, characterized in that The amino group was modified on the surface of the aldehyde-modified Fe3O4@SiO2@GMA-G by the following method: the aldehyde-modified Fe3O4@SiO2@GMA-G was mixed with a mixed solution of ethylenediamine and reacted in a water bath to obtain Fe3O4@SiO2@GMA-G@NH2.
27. The method according to claim 26, characterized in that The ethylenediamine mixed solution is a 40% ethylenediamine mixed solution, with isopropanol and ethanol as solvents.
28. The method according to claim 26, characterized in that The dosage of the ethylenediamine mixed solution is 500 μL.
29. The method according to claim 26, characterized in that The conditions of the water bath reaction are 80° C., 4 h.
30. The method according to claim 1, characterized in that The phosphate groups were modified on the surface of Fe3O4@SiO2@GMA-G@NH2 by the following method: the Fe3O4@SiO2@GMA-G@NH2 was added to an acetonitrile solution containing POCl3 and 2,4,6-trimethylpyridine, and reacted at room temperature for 1 hour to obtain Fe3O4@SiO2@GMA-G@NH2@PO3.
31. The method according to claim 30, characterized in that The dosage of the acetonitrile solution is 500 μL.
32. The method according to claim 30, characterized in that The concentration of POCl3 in the acetonitrile solution is 40 mM.
33. The method according to claim 30, characterized in that The concentration of 2,4,6-trimethylpyridine in the acetonitrile solution is 40 mM.
34. The method according to claim 1, characterized in that The following method was used to 4+ Fixed on Fe3O4@SiO2@GMA-G@NH2@PO3: The Fe3O4@SiO2@GMA-G@NH2@PO3 was resuspended in Ti(SO4)2 solution and reacted at room temperature for 1 h to obtain Fe3O4@SiO2@GMA-G@NH2@PO3@Ti 4+ .
35. The method according to claim 34, characterized in that The dosage of Ti(SO4)2 used is 0.1M, 1mL.
36. A novel composite magnetic nanomaterial modified by grafting phosphate with dextran polymer prepared by the method of any one of claims 1 to 35.
37. Any one of the following applications, characterized in that: The applications include: (1) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate as claimed in claim 36 in enriching and / or separating phosphorylated proteins and / or phosphorylated peptides in a mixture; (2) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate as claimed in claim 36 in enriching and / or separating phosphorylated proteins and / or phosphorylated peptides in cells; (3) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate as described in claim 36 for enriching and / or separating phosphorylated proteins and / or phosphorylated peptides in FFPE samples; (4) Use of the novel composite magnetic nanomaterial modified with dextran polymer grafted with phosphate as described in claim 36 in enriching and / or separating phosphorylated peptides from α-casein cleaved peptides.
38. A method for enriching and / or separating phosphorylated peptides from α-casein cleaved peptides, characterized in that: The method comprises the following steps: dissolving the α-casein cleavage peptide and the novel composite magnetic nanomaterial modified with glucan polymer grafted phosphate as described in claim 36 in a binding buffer solution and mixing them, and incubating them at 37° C. to achieve enrichment of the α-casein cleavage peptide; washing the enriched composite magnetic nanomaterial with two washing buffer solutions, Buffer 1 and Buffer 2, respectively, and eluting the phosphorylated peptide on the composite magnetic nanomaterial with an elution buffer solution to achieve separation of the α-casein cleavage peptide.
39. The method according to claim 38, characterized in that The dosage of the novel composite magnetic nanomaterial modified by glucan polymer grafted with phosphate is 100 μg.
40. The method according to claim 38, characterized in that The binding buffer solution is: acetonitrile / H2O / TFA=80 / 15 / 5, v / v / v, containing 0.1 M lactic acid.
41. The method according to claim 38, characterized in that The washing buffer solution Buffer 1 is: acetonitrile / H2O / TFA=80 / 49 / 1, v / v / v.
42. The method according to claim 38, characterized in that The washing buffer solution Buffer 2 is: acetonitrile / H2O / TFA=10 / 89.8 / 0.2, v / v / v.
43. The method according to claim 38, characterized in that The elution buffer solution is: 10% NH3·H2O.
44. The method according to claim 38, characterized in that The enrichment time is 30 min.
Citation Information
Patent Citations
Method for separating and enriching phosphorylated peptide
CN101101283A
Hair-like hydrophilic polymer hybridization magnetic nanoparticle immobilized enzyme and preparation method thereof
CN103667241A
Hydrophilic chromatographic packing as well as preparation method and application thereof
CN104415740A
Polyethyleneimine-silicon dioxide microsphere with titanium phosphate / zirconium phosphate groups modified on surfaces, and preparation methdo and application thereof
CN112742360A